The Effect of Narrow and Broad Band Ultraviolet B Onto Keloid Fibroblast-VEGF Expressions - Yohanes Widodo Wirohadidjojo Ishandono Dahlan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2007)
Background: Collagenase inactivation of keloid lesions is due to plasminogen activator inhibitors which are synthesized under stimulation of vascular endothelial growth factor (VEGF), a released protein under hypoxia conditions. On the other hand, ultraviolet B (UVB) may generate various oxidative molecules of irradiated chromophores. The effect of UVB in VEGF synthesis is unclear.ObJective. To know the effect of narrow and broad band ultraviolet-B on keloid fibroblast-VEGF expression. Materials and methods: Materials in this study were keloid materials collected from dermatosurgery and plastic surgery keloid revision. A parallel simple experiment study was performed to compare the effect of 0, 50, 75, and 100mJ/cm2 of broad band (BBUVB) as well as narrow band UVB (NBUVB) in VEGF synthesis of passage-3 keloid fibroblasts isolated from 4 patients. Samples were stained with monoclonal antibody anti VEGF. The selected DAB-brown colors of cytoplasm were computed based on Photoshop software histogram.Results: Compared to untreated group, all of various NBUVB showed a very significant (P0.05) between NBUVB and BBUVB groups.Conclusion: NBUVB as well as BBUVB can suppress VEGF synthesis among irradiated keloid fibroblasts. The 50 mJ/cm2 of NB UVB as well as 75 mJ/cm2 of BBUVB may be developed as the modality in keloid prevention or treatment.Keywords: keloid-fibroblasts, broad-band UVB, narrow-band UVB, VEGF